New exact solutions to the generalized nonlinear Schrödinger equation - Zhang, Zaiyun (Array, 2008)
Summary: Using the modified mapping method and the extended mapping method, we derive some new exact solutions of the generalized nonlinear Schrödinger equation, which are linear combinations of two different Jacobi elliptic functions and we also consider the solutions in the limiting cases